IMPACT OF SHELL GINGER LEAF CAPSULE SUPPLEMENTATION FOR 8 WEEKS ON PLASMA MALONDIALDEHYDE AND SELECTED BLOOD BIOCHEMICAL PARAMETERS IN HEALTHY YOUNG MEN IN QUANG NINH (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the impact of Shell Ginger (Alpinia zerumbet) leaf capsules on plasma MDA levels and selected blood biochemical parameters in healthy young men after 8 weeks of supplementation.Methods: A randomized controlled intervention study with a pre-post design was conducted in Quang Ninh province, Vietnam. A total of 55 participants completed the study, including 28 participants in the intervention group and 27 participants in the control group. The intervention group received Shell Ginger capsules (500 mg/capsule) at a dose of 9 capsules per day for 8 weeks, while the control group received no supplementation. Anthropometric parameters, plasma MDA levels, glucose, lipid profiles, and liver and kidney function indicators were assessed before and after the intervention.Results: After 8 weeks, plasma MDA levels decreased significantly in the intervention group, from 2.1 nmol/mL to 1.8 nmol/mL. Post-intervention MDA levels were also significantly lower in the intervention group compared with the control group. Plasma glucose decreased from 5.1 mmol/L to 4.8 mmol/L, and LDL-C decreased from 2.7 mmol/L to 2.2 mmol/L in the intervention group. However, the post-intervention differences in glucose and LDL-C between the two groups were not statistically significant. No significant changes were observed in creatinine, AST, or ALT levels.Conclusions: Shell Ginger capsules may contribute to improving oxidative status through reducing plasma MDA levels after 8 weeks of supplementation, with no evidence of adverse effects on liver or kidney function.
Keywords: Shell Ginger, Alpinia zerumbet, malondialdehyde, MDA, glucose, LDL-C, oxidative stress.